Examination of children’s visuospatial thinking skills in domain-general learning and interpretation of scientific diagrams - Uchinokura, Shingo; Koba, Kengo (Frontiers in Education, 2022)
Visuospatial thinking is a form of thinking that involves the purposeful use of human eyes to develop internal representation. This study examined the visuospatial thinking skills of primary school students with the aims of identifying students who have difficulties with these skills in domain-general learning and discovering how primary school students respond to visuospatial tasks that require interpretation of a diagrammatic representation. The study also investigated whether there are differences in how male and female students answer visuospatial thinking tasks. The participants comprised 93 fourth-grade students (8–9 years old), including 51 male and 42 female students, from a public primary school in Japan. The participants completed two types of paper-pencil tests. The first test required participants to complete the Wide-range Assessment of Vision-related Essential Skills (WAVES), a domain-general test. In the second test, students answered questions about the relationship between the movement of the sun and the behaviours of solar cells located in different places by interpreting a diagrammatic representation. Female students outperformed male students in one of the four WAVES index scores; otherwise, no other statistically significant differences were found. A small number of students had low visuospatial perception scores. When the students were asked to explain their reasoning regarding how the solar cells worked based on their interpterion of the diagram, only a few answered correctly using perspective-taking and/or visualizing. Other students struggled to reason, even if they had factual knowledge. Some students held an alternative conception of sunlight intensity and the sun’s path in the sky. They reasoned the problem from their alternative conceptions without reference to visuospatial information or taking different perspectives from that given in the diagram. No statistically significant differences were found in the relation between achievement in the domain-general test and the number of correct answers in the domain-specific test. The study’s findings imply that students should be taught the concept of space and teach conventional knowledge on different representations, as well as to be encouraged to overcome their alternative conceptions. Further research on students' learning progress in visuospatial thinking that includes alternative conceptions as the students’ domain-specific knowledge is recommended.